Alzheimer's disease - the role of nurses in patient care - Patrycja Polańska (Journal of Education, Health and Sport, 2019)
Alzheimer's disease is the most common degenerative disorder of the brain resulting in dementia. It occurs most frequently among the elderly. This article presents the causes, effects and manner of developing the disease. Described above are the most important aspects of patient care. Particular attention was paid to the adaptation of housing, communication, rehabilitation, diet, forms of support for the patient and caregivers. Due to the nature of care they were also presented specific problems in health and the role of nurses has been determined.